2020
DOI: 10.1155/2020/5726947
|View full text |Cite
|
Sign up to set email alerts
|

Immortalizing Mesenchymal Stromal Cells from Aged Donors While Keeping Their Essential Features

Abstract: Human bone marrow-derived mesenchymal stromal cells (MSCs) obtained from aged patients are prone to senesce and diminish their differentiation potential, therefore limiting their usefulness for osteochondral regenerative medicine approaches or to study age-related diseases, such as osteoarthiritis (OA). MSCs can be transduced with immortalizing genes to overcome this limitation, but transduction of primary slow-dividing cells has proven to be challenging. Methods for enhancing transduction efficiency (such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 76 publications
3
17
0
Order By: Relevance
“…In this study, primary MSCs derived from aged donors were immortalized by sequential spinoculation of SV40LT and hTERT, as previously described [ 30 ]. Immortalized MSCs overcame senescence and acquired an unlimited proliferation potential while maintaining most of the characteristics of MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, primary MSCs derived from aged donors were immortalized by sequential spinoculation of SV40LT and hTERT, as previously described [ 30 ]. Immortalized MSCs overcame senescence and acquired an unlimited proliferation potential while maintaining most of the characteristics of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of CD105 was higher in iMSCs and T-MSCs than in primary MSCs. We have previously observed that CD105 can either reduce or increase its expression from primary to immortalized cells [ 30 ], and its expression can also be reduced with passaging [ 29 , 33 , 34 , 35 , 36 ]. The role that CD105 expression plays in MSCs is still unclear [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC immortalization can be achieved by the combination of transduction of immortalizing genes such as simian virus 40 large T antigen (SV40LT), which promote cell cycle progression and human telomerase reverse transcriptase (hTERT) and prevent telomeres shortening [ 286 ]. In addition, both morphology and functionality of MSC were found to not change after transduction of immortalization genes [ 285 , 287 ].…”
Section: Need Of New Strategies Of Msc Productionmentioning
confidence: 99%
“…In these lines, cells can be produced in large amounts and grown indefinitely, offering a good tool to explore molecular and biochemical processes [ 9 ]. Numerous immortalized cell lines have been generated from MSCs, bone cells, muscle cells and chondrocytes [ 22 , 23 , 24 ], which have provided valuable information about the processes involved in skeletal development. However, these cell lines may contain genetic and metabolic abnormalities due to their derivation using mainly integrative methods.…”
Section: Introductionmentioning
confidence: 99%